Everything Never Comes Your Way - O'Donnell, Nicole Stellon (Book collections on Project MUSE., 2021)
"In her third collection, Nicole Stellon O'Donnell explores the landscapes of memory, argument, and wilderness. These poems deconstruct memoir, dig at the roots of philosophical argumentation, and critique the role of the poet as an observer of the natural world. From manicured baseball fields to the debate podium, from the lobby of the public pool to the hallowed Alaskan cabin where John Haines once sat down to write, these poems push against the notion that the solitary self is the arbiter of truth"--